MENA Quarterly Economic Brief, July 2015 : Economic Implications of Lifting Sanctions on Iran - Devarajan, Shanta; Mottaghi, Lili (World Bank, Washington, DC, 2015)
Iran and the Permanent Members of the UN Security Council and Germany (P5+1) reached a deal on July 14, 2015 that limits Iranian nuclear activity in return for lifting all international sanctions that were placed on Iran (Box 1). This issue of the MENA Quarterly Economic Brief (QEB) traces the economic effects of this development—removing sanctions on Iran—on the world oil market, on Iran’s trading partners, and on the Iranian economy.